The extensor digitorum brevis manus variability and clinical significance: a systematic review with meta-analysis. - Triantafyllou, George; Piagkou, Maria; Paschopoulos, Ioannis; Duparc, Fabrice; Tsakotos, George; Georgiev, Georgi P. (Surgical & Radiologic Anatomy, 2025)
Purpose: The current meta-analysis aimed to investigate the extensor digitorum brevis manus (EDBM) muscle variability by calculating the pooled prevalence of all published variants. After considering the pooled prevalence, these variants were classified based on their insertion and relationship with the extensor indicis (EI) muscle and/or tendon. The origin of the variants, neural and arterial supply, and the terminology of the EDBM variants were further investigated. Materials: The systematic review was conducted according to the guidelines proposed by the Evidence-Based Anatomy Workgroup and PRISMA 2020. Four databases were searched using several keyword combinations. The included studies were statistically meta-analyzed using the R programming language. The EDBM pooled prevalence was calculated, as were subgroup analyses of a few parameters. Results: Thirty-one studies met our inclusion criteria, with a total sample of 9686 hands. The EDBM pooled prevalence was estimated at 1.96% (95%CI 1.42–2.58). The EDBM's most common insertion was via a distinct tendon to the index finger, coexisting with the typical EI tendon (0.38% pooled prevalence). The origin, innervation, and arterial supply of EDBM have not been studied systematically. Conclusions: The EDBM variant can be considered infrequent, with a pooled prevalence of 1.96%. Particular attention should be given to the muscle’s insertion and relationship with the EI muscle and tendon. Knowledge of the EDBM morphological variability is adequate for hand and reconstructive surgeons to avoid confusion intraoperatively and misdiagnosis preoperatively.